The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1995
DOI: 10.1021/bi00051a026
|View full text |Cite
|
Sign up to set email alerts
|

Membrane thinning caused by magainin 2

Abstract: Magainin 2 is a 23-residue antibiotic peptide found in the skin of Xeonpus laevis (African clawed frog). It belongs to a broad class of alpha-helical peptides which interact directly with the lipid bilayer. Very little is presently known about the nature of this peptide/lipid interaction on the molecular level. We have performed a sequence of lamellar X-ray diffraction experiments to provide some insight into the nature of this interaction. We have found that, at concentrations below the critical concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

29
288
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 307 publications
(318 citation statements)
references
References 20 publications
29
288
1
Order By: Relevance
“…A membrane area increase, ∆A, causes a thinning of the chain region, -∆h, by the relation -∆h/h ) ∆A/A. Indeed, we have found that in all cases the bilayer thickness decreases linearly with increasing P/L (34,37,38,42,53) until P/L reaches a critical value, (P/L)*. Thus the slope of the membrane thickness versus P/L below (P/L)* (Figure 6) gives the value of A P ( Table 1).…”
Section: Experimental Parametersmentioning
confidence: 67%
“…A membrane area increase, ∆A, causes a thinning of the chain region, -∆h, by the relation -∆h/h ) ∆A/A. Indeed, we have found that in all cases the bilayer thickness decreases linearly with increasing P/L (34,37,38,42,53) until P/L reaches a critical value, (P/L)*. Thus the slope of the membrane thickness versus P/L below (P/L)* (Figure 6) gives the value of A P ( Table 1).…”
Section: Experimental Parametersmentioning
confidence: 67%
“…Skin permeability to fluorescein was significantly increased (Student's t-test, p<0.01), but permeability to the two larger molecules was not significantly affected by magainin (Student's t-test, p>0.05). This can be explained because magainin is believed to form Angstrom-scale pores across lipid bilayers that are known to be large enough for transport only of small molecules [9,10].…”
Section: Resultsmentioning
confidence: 99%
“…Then Fourier Shell Correlation (FSC) was calculated between both maps applying the 0.5 FSC threshold. Second, we performed the even-odd test in EMAN 37,39 in which two maps were obtained following the last cycle of refinement from the even and odd numbered particles and compared by FSC.…”
Section: Three-dimensional Reconstruction and Visualization Of Mapsmentioning
confidence: 99%